THE IMPORTANCE AND PROSPECTS OF DIGITALIZATION IN TAX ADMINISTRATION (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The digitalization of tax administration represents a paradigm shift in the way governments collect revenue and interact with taxpayers. This article examines the importance and prospects of this transformation, drawing on a comprehensive review of existing literature. Adopting a clear academic structure, this paper synthesizes findings from over ten academic and institutional sources to explore the multifaceted impacts of digitalization on tax systems worldwide. The review reveals that digitalization significantly enhances efficiency, transparency, and tax compliance, while also presenting challenges related to implementation, data security, and the digital divide. The prospects for the future of tax administration are intrinsically linked to emerging technologies such as artificial intelligence (AI), blockchain, and big data analytics, which promise to further revolutionize the field. This article provides a nuanced understanding of the current landscape and future trajectory of digital tax administration, offering valuable insights for policymakers, tax practitioners, and researchers.